Strategi Pemulihan UMKM Kuliner Pasca Pandemi Covid-19 - Mellinia, Salma Putri; Setyorini, Christina Tri; Budiarti, Laeli (Politeknik Negeri Ambon, 2023)
The purpose of this study is to determine the recovery strategy of culinary MSMEs after the Covid-19 pandemic in Purwokerto City. This research is a qualitative research with phenomenological approach. The informants in this study is 6 owners of culinary MSMEs in Purwokerto City using purposive sampling method. Interviews and observations are the types of data collection in this study. The data validity test in this study uses triangulation of theory. Data analysis techniques used by researcher are data reduction, data presentation, and conclusion drawing. The results of this study show that all informants have carried out business recovery strategies. The recovery strategies include providing discount promos, using technology-based production tools, conducting online promotions, and keeping business financial records.